DARI LINI KE LINGKAR: EKSPLORASI CIRCULAR FASHION DALAM DESAIN MERCHANDISE SEBAGAI STRATEGI GREEN BRANDING UNIVERSITAS - Silmy Fadhilah; Irma Russanti; Fadlilah Indira Sari; Yuhri Inang Prihatina (Universitas Negeri Surabaya, 2026)
Circular fashion is a concept that emphasizes sustainable fashion by utilizing waster materials to create new higher value product through upcycling. This upcycling principle has a positive impact on the environment by reducing waste and enhancing ther green branding of D4 Tata Busana study program. This study aims to evaluate the implementation of circular fashion in a merchandise prototype that represents the identity of the D4 Tata Busana study program. The ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation, was employed to assess how circular fashion designs strengthen the institution's identity. The development object consists of fashion miniature merchandise made from patchwork fabric waste generated through Teaching Factory (Tefa) practical activities. This study developed four merchandise prototypes for the D4 Fashion Design Study Program, with one prototype selected, earning a score of 37.5%. The evaluation involved 56 respondents and focused on two criteria: (1) originality and novelty, and (2) production needs feasibility. The evaluation results suggest that the chosen merchandise design is suitable for production, as 66% of respondents see the product as innovative. This study demonstrates the potential to develop an income-generating product with efficient production practices costs.